Fetuin A levels and its correlation with lipid profile in type 2 diabetes mellitus patients (Panacea Journal of Medical Sciences, 2022)
Introduction: Type 2 diabetes mellitus (T2DM), is a chronic metabolic disorder. Due to its complex pathophysiology, several biomarkers have been studied for identifying its complications. Fetuin A has been proposed to be linked with insulin resistance and its comorbidities and may be helpful in understanding the pathophysiology of the disease condition. Therefore, the present study is aimed to evaluate the Fetuin A levels in Type 2 diabetes mellitus patients and its correlation with blood sugar, renal profile and lipid profile.Materials and Methods: This prospective study was conducted in SRVS Government Medical College, Shivpuri, Madhya Pradesh, India. In this study, 90 T2DM patients as cases and 90 healthy subjects as controls were recruited. Demographic details, physical and clinical examination were done. Patients with cardiovascular diseases, thyroid diseases, liver disease, pregnant women were excluded from the study. Under aseptic conditions, 5 ml of fasting venous blood samples were collected, centrifuged to obtain serum sample. The obtained serum sample was used for the estimation of fasting glucose, post-prandial glucose, renal profile (serum urea, creatinine and uric acid), lipid profile (serum total cholesterol, triglycerides, HDLC, LDLC and VLDL) using commercially available autoanalyzer kits. Serum Fetuin A levels were estimated by using ELISA method. Whole blood sample was used for the estimation of HbA1c. The results were represented as Mean±SD. and percentage. Spearman’s correlation was applied. The p value  Results: In this study, in T2DM cases, males were 51 and females were 39 and in controls, males were 50 and females were 40. In the current study, age (63.8±5.7 years), BMI (26.2±1.6 kg/m) SBP (130.8±13.2 mmHg), DBP (90.6±12.7 mmHg), FBS (158.7±14.5 mg/dl), PPBS (228.5±31.8 mg/dl), HbA1c (7.8±0.7 %), Urea (32.1±9.4 mg/dl), Creatinine (1.0±0.1 mg/dl), Uric acid (6.2±2.8 mg/dl), total cholesterol (228.4±33.0 mg/dl), triglycerides (160.0±15.2 mg/dl), LDLC (165.6±33.6 mg/dl), VLDL (32.0±3.0 mg/dl) and Fetuin A (363.9±126.2 micg/ml) levels were significantly increased and HDLC (30.7±3.9 mg/dl) levels were reduced in T2DM cases than the healthy controls. Fetuin A level were significantly positively correlated with FBS (r=0.686), PPBS (r=0.656), HbA1c (r=0.694), Urea (r=0.342), Creatinine (r=0.564), Uric Acid (r=0.588), Total Cholesterol (r=0.700), Triglycerides (r=0.405), LDLC (r=0.728), and VLDL (r=0.528) and negatively correlated with HDLC (-0.681).Conclusion: Elevated fetuin A and atherogenic lipid profile may be a risk for cardiometabolic diseases.